Advancement level of mobile applications intended for type 1 diabetes therapy supporting - Tomasz Jerzy Nowicki; Grzegorz Józef Nowicki; Barbara Ślusarska (Kazimierz Wielki University, 2020)
Diabetes mellitus is a group of metabolic diseases characterized by hyperglycaemia due to defective secretion and/or action of insulin. Chronic hyperglycaemia is associated with damage, dysfunction, and failure of various organs, in particular eyes, kidneys, nerves, heart, and blood vessels.  It is estimated that the number of patients with type 1 diabetes accounts for about 10% of all diabetics, even more children and young adults i.e. under 30 constitute between 85 - 90 % of morbidities.  The fundamental part of type 1 diabetes therapy is providingpatient with an external insulin therapy. The objective of this research was to formulate requirements concerning mobile applications for diabetes 1 therapy as well as an overview and a classification of such applications currently available. This paper includes a set of 20 requirementsfor mobile applications intended for type 1 diabetes patients. Some of them are beyond the possibilities of the modern-day IT industry. Nowadays there is no applications that meets all of the criteria. However, the tendency to fulfill all of them can be noticed.